2007
DOI: 10.1161/circulationaha.106.677369
|View full text |Cite
|
Sign up to set email alerts
|

View-Synchronized Robotic Image-Guided Therapy for Atrial Fibrillation Ablation

Abstract: Background-A robotic catheter navigation system has been developed that provides a significant degree of freedom of catheter movement. This study examines the feasibility of synchronizing this robotic navigation system with electroanatomic mapping and 3-dimensional computed tomography imaging to perform view-synchronized left atrial (LA) ablation. Methods and Results-This study consisted of a porcine experimental validation phase (9 animals) and a clinical feasibility phase (9 atrial fibrillation patients). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 20 publications
1
73
0
Order By: Relevance
“…In conventional VIS, surgeons operate catheter manually in operating room, so there are some disadvantages [1][2]. Firstly, the surgeons are exposed to X-ray for long time, which are harmful to their health.…”
Section: Tsai@buaaeducnmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional VIS, surgeons operate catheter manually in operating room, so there are some disadvantages [1][2]. Firstly, the surgeons are exposed to X-ray for long time, which are harmful to their health.…”
Section: Tsai@buaaeducnmentioning
confidence: 99%
“…Treat the catheter as a rigid body; the pulse number sent to the translation motor, 1 P in correspondence with the theoretical displacement of the catheter can be calculated using (5), which is derived by (1):…”
Section: Accuracy and Precision Of Catheter Operating Robot Evaluatiomentioning
confidence: 99%
“…The overall effect is that operators can manipulate catheters from a distance using a 3D navigation handle. 14 Potential advantages of these technologies include increased safety, more precise catheter manipulation and increased stability. 15 A number of studies have demonstrated that the results of PV isolation with remote navigation are comparable with conventional ablation techniques.…”
Section: Remote Navigation Technologies For Af Ablationmentioning
confidence: 99%
“…Navigation in the left atrium is relatively easy and intuitive in most cases. 55,56 Rarely, a patient's anatomy does not allow the outer mechanical sheath to sit well on the septum. This results in movement much like a manual catheter with a sheath that has fallen to the right atrium.…”
Section: Burkhardt and Natale New Technologies In Atrial Fibrillationmentioning
confidence: 99%